2007
DOI: 10.1111/j.1365-3164.2007.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of papillomaviral sequences in feline Bowenoid in situ carcinoma using consensus primers

Abstract: Feline Bowenoid in situ carcinoma (BISC) is a rare disease that presents as multiple discrete plaques of epidermal hyperplasia and dysplasia. Two studies using immunohistochemistry revealed papillomaviral antigens in 11% and 47% of BISCs. Additionally, a recent study detected papillomaviral DNA in 24% of BISC lesions. To further investigate the association between papillomaviruses and BISC, polymerase chain reaction using consensus primers was used to detect papillomaviral DNA in 18 formalin-fixed samples of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
138
2
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(145 citation statements)
references
References 24 publications
(94 reference statements)
4
138
2
1
Order By: Relevance
“…At the same time, it is becoming increasingly evident that other types of HPVs, particularly those belonging to genus beta, could be involved in nonmelanoma skin cancer, mainly squamous cell carcinoma (SCC), even though their putative etiologic role still remains unclear [6][7][8][9]. PVassociated basosquamous carcinoma has also been reported in an Egyptian fruit bat [10]; likewise, PV DNA sequences have been found in feline Bowenoid in situ carcinoma, a rare disease in cats that presents as multiple discrete plaques of epidermal hyperplasia and dysplasia [11]. Furthermore, current findings strongly support a potential active role of HPVs in the development of malignant melanoma [12][13].…”
mentioning
confidence: 97%
“…At the same time, it is becoming increasingly evident that other types of HPVs, particularly those belonging to genus beta, could be involved in nonmelanoma skin cancer, mainly squamous cell carcinoma (SCC), even though their putative etiologic role still remains unclear [6][7][8][9]. PVassociated basosquamous carcinoma has also been reported in an Egyptian fruit bat [10]; likewise, PV DNA sequences have been found in feline Bowenoid in situ carcinoma, a rare disease in cats that presents as multiple discrete plaques of epidermal hyperplasia and dysplasia [11]. Furthermore, current findings strongly support a potential active role of HPVs in the development of malignant melanoma [12][13].…”
mentioning
confidence: 97%
“…17 Six papillomaviruses have been amplified and sequenced from feline BISCs; one had 97% similarity to HPV isolate FAIMVS14, while the others were all a novel unique virus that was most closely related to HPV type 17. 8 Considering the close contact of cats with humans and the large number of HPV types, it is perhaps not surprising that HPVs can occasionally infect cats. A recent study of papillomaviruses identified from dogs also reported papillomaviruses that were closely related to HPVs.…”
mentioning
confidence: 99%
“…Amplicons were sequenced as previously described. 13 The jmpSA primers amplified PV DNA from 6 of the 7 feline sarcoid samples (86%) but none of the 120 nonsarcoid feline samples. All 6 amplicons were between 97% and 99% similar.…”
mentioning
confidence: 99%
“…13 DNA was also extracted from 36 formalin-fixed, cutaneous samples (18 invasive squamous cell carcinomas, 4 fibrosarcomas, 4 biopsies of allergic dermatitis, 3 biopsies of normal skin, 2 cases of feline leprosy, 2 feline mast cell tumors, 2 apocrine gland cystadenomas, and a follicular cyst) and 16 oral samples (8 cases of plasmacytic stomatitis, 5 eosinophilic granulomas, 2 cases of glossitis, and a case of periodontal disease). Skin and oral swabs were collected from 16 clinically healthy cats with the skin of a further 36 clinically healthy cats also swabbed.…”
mentioning
confidence: 99%